PENERAPAN ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) DAN KEPMENKES RI NO 1204 TAHUN 2004 PADA KLINIK RAWAT INAP KUSUMA HUSADA - Rodliyah, Siti; Setyaningsih, Nina Dwi (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
EMA can improve economic performance and business environment, and can assist manager decision making in an effort to control environmental costs. EMA has 2 types of information that is physical information and monetary information. This reaserch to determine the application of EMA, EMA effect in improving economic and environmental performance, and implementation of KepMenKes RI No 1204 Year 2004 in KRI Kusuma Husada.